Prospective pilot study of tirofiban in progressive stroke after intravenous thrombolysis - Zhang, Yan; Wang, Jianliang; Ma, Zhaoxi; Mu, Guihua; Liang, Da; Li, Yifan; Qian, Xiaoyan; Zhang, Luyuan; Shen, Fang; Zhang, Lei; Yu, Jie; Liu, Yang (Frontiers in Neurology, 2022)
Background Intravenous thrombolysis (IVT) is a standard procedure for the treatment of patients with acute ischemic stroke (AIS). Improving the therapeutic efficacy of IVT is an important task for neurologists. The aim of this study was to evaluate the efficacy and safety of early low-dose tirofiban treatment in AIS patients with early neurological deterioration (END) after IVT. Methods In this prospective and randomized pilot study, 73 AIS patients with END were recruited from a local hospital in China. Of these, 14 patients were treated with regular antiplatelet agents (aspirin plus clopidogrel) and 59 patients were treated with tirofiban within 24 h of IVT, followed by regular antiplatelet therapy. Neurological deficits and functional recovery were assessed with NIHSS and modified Rankin Scale (mRS) at 7 and 90 days. During the 90-day follow-up period, both hemorrhagic (e.g., intracerebral hemorrhage) and non-hemorrhagic (e.g., pneumonia) events were recorded. Results Treatment with tirofiban compared with regular antiplatelet therapy: (1) improved functional recovery of AIS patients to mRS (≤2) at both 7 and 90 days (odds ratios [ORs], 1.37 and 1.64; 95% confidence interval [CI], 1.16–1.61 and 1.26–2.12; P = 0.008 and < 0.001, respectively), and (2) reduced NIHSS scores from 11.14 ± 2.38 to 5.95 ± 3.48 at day 7 (P < 0.001) and from 8.14 ± 2.74 to 4.08 ± 3.50 at day 90 (P < 0.001). Tirofiban treatment did not increase the risk of hemorrhagic complications. Multivariate regression analysis showed that tirofiban treatment independently predicted a favorable functional outcome (P ≤ 0.001). Conclusion Early treatment with low-dose tirofiban in AIS patients with neurologic deterioration after IVT potentially improved functional recovery and attenuated neurologic deficits as early as 7 days and did not increase the risk of various hemorrhagic complications. However, the therapeutic efficacy of tirofiban treatment in END patients needs to be determined by future randomized clinical trials with a large study population. Clinical trial registration http://www.chictr.org.cn/, Identifier ChiCTR2200058513.